2017
DOI: 10.4236/ce.2017.89097
|View full text |Cite
|
Sign up to set email alerts
|

Systems Structure of Education for Sustainable Development in Higher Education Institution

Abstract: To understand the enactment of Education for Sustainable Development (ESD) in higher education institution (HEI) and why very unequal ESD activity that mostly focused on campus greening rather than on pedagogic reform in HEI requires more than simply an examination of the ESD curriculum and pedagogy. To grasp why and how ESD is implemented in a HEI, the contexts in which it was created and implemented should be considered. Systems structures that include the context of the phenomena can show how the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Educators are able to improve knowledge of sustainability and identify its relevance in the subject being taught by learning and doing research with their students. Mahmud (2017) also stated that it is difficult to convince academic staff who have no sustainability discipline to accept the concept of sustainable development because they consider the topic of sustainability as irrelevant to their discipline. Encouragement from the administrators is necessary to give educators the confidence to integrate the concept of sustainable development.…”
Section: Resultsmentioning
confidence: 99%
“…Educators are able to improve knowledge of sustainability and identify its relevance in the subject being taught by learning and doing research with their students. Mahmud (2017) also stated that it is difficult to convince academic staff who have no sustainability discipline to accept the concept of sustainable development because they consider the topic of sustainability as irrelevant to their discipline. Encouragement from the administrators is necessary to give educators the confidence to integrate the concept of sustainable development.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, João Marcelo Pereira Ribeiro et al, (2021) in Brazil agree that implementing sustainable development (SD) dissemination strategies in universities enhances students' understanding and awareness of SD significance. However, Mahmud (2017) in Malaysia states that a lack of awareness among the important stakeholders in curriculum development is a barrier to implementing ESD. However, the study results indicate that students recognize that curricula and courses in their universities are designed to support and advance sustainable development practices.…”
Section: Discussionmentioning
confidence: 99%
“…This does not mean that school-level factors do not play a strong role in motivating teachers, but it seems that in the Malaysian context, the Ministry of Education has taken appropriate steps to eliminate and/or reduce school-level barriers that no longer become a hindrance to embedding ICTeEfS. It has been shown that the enactment of Education for Sustainability (EfS) in Malaysian education has mostly focused on school/campus greening rather than on pedagogic reform [63], which may explain the strong predictive effect of teacher-system-level barriers. To grasp why and how EfS is being implemented in education, the teacher and system structures and contexts need to be highly considered by education policymakers.…”
Section: Discussionmentioning
confidence: 99%